PHYSICO-CHEMICAL ASSESSMENT OF SURFACE AND GROUNDWATER QUALITY IN SAVANNAH SUGAR COMPANY, NUMAN AND ITS ENVIRONS, ADAMAWA STATE, NIGERIA - Ijantiku, Joseph; Mohammed, Abdulaziz; Lukas, Martin; Seli, Ahmed Buba (FUDMA JOURNAL OF SCIENCES, 2025)
This research is aimed at evaluating surface and groundwater quality around the Savannah Sugar Company, Numan, and its environs. The analysis indicated that total hardness ranged from 43.9-91.0 mg/L and DO ranged from 4.2-11.3 mg/L, BOD ranged from 6.6-116.0 mg/L, and COD 10.4-139 mg/L, while Nitrate varied from 4.1-80.1 mg/L. Spatial analysis indicated a significant concentration of nitrate and iron at the northwestern flank of the study area.  pH varied from 5.3 to 9.2, Electric conductivity (EC) 178-605 µS/cm; TDS ranged from 115-401 mg/L. Fe, Cu, Mn, Zn were below WHO/FMEnv limits, with iron (Fe) reflecting an average of 0.3 mg/L; while others were
Keywords: Physico-chemical; Groundwater; Surface water; Savannah sugar; Water quality